Effect of hyperbaric oxygen therapy on postoperative muscle damage and inflammation following total knee arthroplasty: a randomized controlled trial - Ruinian Zhang; Hang Guo; Shangkun Tang; Jingjing Zuo; Xiaojun Shi (Scientific Reports)
Abstract This study aims to investigate the effect of hyperbaric oxygen therapy (HBOT) on muscle damage and inflammatory responses after total knee arthroplasty (TKA). This study selected 80 patients requiring TKA for primary knee osteoarthritis from July 2023 to December 2023 and equally randomized them into two groups—the HBOT and control groups—with 40 patients in each group. The HBOT group received standard treatment supplemented with HBOT, whereas the control group received normobaric oxygen therapy. Muscle damage markers, including glutamic oxaloacetic transaminase (GOT), creatine kinase (CK), lactate dehydrogenase (LDH), and myoglobin (Mb), as well as inflammatory responses were compared preoperatively and 1, 3, and 14 days postoperatively. Additionally, limb circumference, quadriceps muscle strength, and the range of motion (ROM) of the affected limb were measured preoperatively and postoperatively. Any adverse events were documented. The HBOT group demonstrated a significant reduction in muscle damage 3 days post-TKA compared with the control group. A statistically significant acceleration in the recovery of quadriceps muscle strength and a decrease in the ratio of postoperative limb swelling accompanied this reduction. The HBOT group demonstrated a statistically significant alleviation of inflammatory responses 3 days postoperatively compared to the control group. Additionally, the visual analog scale (VAS) scores decreased for both rest and motion 2 and 3 days postoperatively, indicating an improved early ROM. Notably, no significant differences in postoperative adverse events were found between the two groups. The use of HBOT in the postoperative care of patients undergoing TKA has proven to be effective in mitigating muscle damage and alleviating inflammatory responses. Trial registration: Chinese Clinical Trial Registry (ChiCTR2300072685). Registered 21/6/2023, ULR of trial registry: https://www.chictr.org.cn/bin/project/edit?%20pid=198904 .